2004
DOI: 10.14219/jada.archive.2004.0207
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols and splatter in dentistry

Abstract: In addition to the routine use of standard barriers such as masks and gloves, the universal use of preprocedural rinses and high-volume evacuation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
337
0
23

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(364 citation statements)
references
References 19 publications
4
337
0
23
Order By: Relevance
“…Ultrasonic scalers, hand pieces and air polishers, commonly used in the dental clinic, produce aerosols that contain blood, saliva, calculus, restorative materials, and pathogenic microorganisms, rendering the dental clinic a hazardous environment. For this reason, cross-contamination is a frequently discussed issue in the dental field 4–6. In fact, such aerosols may cause the transmission of tuberculosis, common cold, influenza, herpetic viruses’ infection, hepatitis B and C, and HIV 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic scalers, hand pieces and air polishers, commonly used in the dental clinic, produce aerosols that contain blood, saliva, calculus, restorative materials, and pathogenic microorganisms, rendering the dental clinic a hazardous environment. For this reason, cross-contamination is a frequently discussed issue in the dental field 4–6. In fact, such aerosols may cause the transmission of tuberculosis, common cold, influenza, herpetic viruses’ infection, hepatitis B and C, and HIV 4.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, cross-contamination is a frequently discussed issue in the dental field 4–6. In fact, such aerosols may cause the transmission of tuberculosis, common cold, influenza, herpetic viruses’ infection, hepatitis B and C, and HIV 4. Variability of infectious aerosols produced during coughing by patients with pulmonary tuberculosis 7…”
Section: Introductionmentioning
confidence: 99%
“…The performed studies mainly concentrated on the infection risk of dental workers due to their frequent exposure to bioaerosols (Nejatidanesh et al, 2013;Kadaifciler and Cotuk, 2014). A direct relationship between bioaerosols produced during dental procedures and the respiratory system infections has been demonstrated (Harrell and Molinari, 2004). It has been also proved that microorganisms present in a dental office, which may include pathogenic bacteria, viruses and fungi, may be responsible for the transmission of highly infectious diseases, not only to the dental personnel, but also to patients (Szymańska and Sitkowska, 2012;Kadaifciler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kolenbrander et al (2002) [18] reported that 500 -700 types of bacterial species can be found in the mouth and since these bacteria are not normally found elsewhere in the body most are considered pathogenic. The mouth is a prime source for spreading infectious diseases (CDC, 2014) [19] and five infectious diseases are spread by oral saliva (Harrel and Molinari, 2004) [20] some of which are life-threatening (Sumi et al, 2006) [21]. Bacterial populations of saliva were approximately 1 million bacteria per mL (Trevino et al, 2009) [22].…”
Section: Resultsmentioning
confidence: 99%